2019
DOI: 10.1080/23273798.2019.1642498
|View full text |Cite
|
Sign up to set email alerts
|

Mutual attraction between high-frequency verbs and clause types with finite verbs in early positions: corpus evidence from spoken English, Dutch, and German

Abstract: We report a hitherto unknown statistical relationship between the corpus frequency of finite verbs and their fixed linear positions (early vs. late) in finite clauses of English, Dutch, and German. Compared to the overall frequency distribution of verb lemmas in the corpora, high-frequency finite verbs are overused in main clauses, at the expense of nonfinite verbs. This finite versus nonfinite split of high-frequency verbs is basically absent from subordinate clauses. Furthermore, this "main-clause bias" (MCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Prior studies believed high-frequency words may reflect specific linguistic patterns in certain domains which would benefit EFL speakers in more effective acquisition of domain knowledge when reading English texts. 3,5,6,43,44 Thus, with rapid information flow of COVID-19, establishing COVID-19 specialized corpus for timely acquisition of updated medical knowledge is especially critical for medical care personnel. 7,9,11,14,32 Certainly, as of the end of October 2020, more than 38,000 RAs on COVID-19-related topics had been published in the WOS database; this phenomenon indicated that a large number of research results were produced by leading researchers globally.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies believed high-frequency words may reflect specific linguistic patterns in certain domains which would benefit EFL speakers in more effective acquisition of domain knowledge when reading English texts. 3,5,6,43,44 Thus, with rapid information flow of COVID-19, establishing COVID-19 specialized corpus for timely acquisition of updated medical knowledge is especially critical for medical care personnel. 7,9,11,14,32 Certainly, as of the end of October 2020, more than 38,000 RAs on COVID-19-related topics had been published in the WOS database; this phenomenon indicated that a large number of research results were produced by leading researchers globally.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional corpus‐based computing methods for critical word ranking mainly calculate words' frequency values and rank them. Prior studies believed high‐frequency words may reflect specific linguistic patterns in certain domains which would benefit EFL speakers in more effective acquisition of domain knowledge when reading English texts 3,5,6,43,44 . Thus, with rapid information flow of COVID‐19, establishing COVID‐19 specialized corpus for timely acquisition of updated medical knowledge is especially critical for medical care personnel 7,9,11,14,32 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This corresponds to recent findings from spoken adult corpora in German, Dutch, and English, where finite forms are much more frequent than nonfinite forms, but also lexically restricted to a small set of high-frequency, but semantically light verbs or auxiliaries. Kempen and Harbusch (2019) argue that the predominance of only a few high-frequency verbs early in the utterance facilitates processing. When looking at their list of the 50 most frequent German finite verbs in written corpora, it seems that many of them are not typical in CDS such that the set of high-frequency finite verbs addressed to children should be even smaller.…”
Section: Predictions For the Acquisition Of Specific Domainsmentioning
confidence: 99%